Urinary bacterial profile and antibiotic susceptibility pattern among pregnant women at Rahima Moosa Mother and Child Hospital - Orji, Ogbonnaya (My University, 2021)
Background: Urinary tract infection (UTI) in pregnancy is associated with significant morbidity for both the mother and the fetus. The aim of this study wasto determine the prevalence, urinarybacterial susceptibility,and resistance patterns among pregnant women with a possible UTI at Rahima Moosa Mother and Child Hospital (RMMCH) in Johannesburg. Methods: This was a retrospective, cross-sectional study describing urine microscopy, sensitivity and culture (MC&S) results from the National Health Laboratory Services data and a medical record review at the RMMCH from January 2017 to December 2017. Results: Urine microscopy, cultures and sensitivities were performed on 1984 specimens belonging to pregnant women who presented with symptoms and/signs of a UTI. Three hundred and thirty-three (16.8%) had positive bacterial cultures. Escherichia coli was the commonest bacterial isolate (50.1%). Other microorganisms isolated included Klebsiella species (14.4%) and Enterococcus faecalis (12.9%). Approximately 98% of organisms were sensitive to cephalexin/ cefazolin. Cefuroxime (95.2%), ceftriaxone/cefotaxime (94.4%) and nitrofurantoin (81.9%) demonstrated microbiocidal effectiveness as indicated. Most bacteria were resistant to ampicillin (84.4%), cotrimoxazole (55.6%) and amoxicillin/clavulanic acid (co-amoxiclav)(50.2%). Conclusion: Escherichia coliwas the commonest pathogen causing UTIs in pregnancy with Enterococcus faecalis increasing in prevalence. Cephalexin / cefazolin, cefuroxime, ceftriaxone / cefotaxime, and nitrofurantoin had the best microbiocidal activities against the organisms causing UTI in pregnant women.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in Obstetrics and Gynaecology.